Food Security, Maternal Knowledge, and Child Nutrition: Bibliometric Insights into Global and Regional Research Trends (2015–2025) - Ida Gelora Sihombing; Syamsul Arifin; Mohammad Bakhriansyah; Edi Hartoyo; Meitria Syahadatina Noor (Universitas Malahayati Lampung, 2025)
ABSTRACT This study aims to analyze the scientific development and global research trends regarding the interrelationship among food security, maternal knowledge, and child nutrition during the period 2015–2025. The background of this research is grounded in the persistent high prevalence of stunting and child malnutrition across various countries, making food security and maternal nutrition literacy critical focuses in sustainable development. This study employs a bibliometric approach, with data obtained using the Publish or Perish software based on Crossref, complemented by institutional repositories and official reports from WHO, FAO, and UNICEF. A total of 100 of the most relevant publications were analyzed using VOSviewer through co-occurrence mapping, network visualization, overlay visualization, and density visualization. The analysis revealed four main clusters: (1) child malnutrition and health determinants, (2) household food security and nutrition, (3) maternal knowledge and feeding practices, and (4) contextual and temporal factors. The findings indicate that child nutrition issues—particularly stunting—have become the focal point of global research closely associated with household food security and maternal knowledge. Publication trends increased during the COVID-19 pandemic, with a strong emphasis on the socioeconomic impacts on child nutrition. Nevertheless, existing studies remain dominated by observational research, with limited longitudinal analyses and geographical diversity. This study concludes that a more integrative and interdisciplinary approach is required to strengthen the scientific evidence supporting the development of sustainable nutrition and food security policies. Keywords: Food Security, Maternal Knowledge, Child Nutrition, Bibliometric Analysis, Stunting.